Pengomposan Sampah Kulit Nanas, Kotoran Ayam, Dan Kotoran Sapi Menggunakan Larva Black Soldier Fly (BSF) - Ayu Nindyapuspa; Vivin Setiani; Tanti Utami Dewi; Ulvi Pri Astuti; Rachma Dinihaque Pristantia Putri (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2022)
Pineapple production which reaches 8.75% of the total production of all fruits in Indonesia produces pineapple peel waste that has not been processed. Therefore, composting with Black Soldier Fly (BSF) larvae was carried out to overcome this problem. Variations in the composition of the compost material used in this study were one hundred percent pineapple peel, a mixture of pineapple skin and cow dung (25:75), and a mixture of pineapple skin and chicken manure (25:75). Temperature, pH, moisture content, C/N and final weight of BSF larvae were analyzed. The weight of the larvae used in each composition of the compost material is fourteen grams. The results showed that the temperature, pH, and moisture content of the compost had met the requirements according to Indonesian National Standard number 19-7030-2004. The C/N ratio of compost with 100% pineapple peel, pineapple skin and cow dung (25:75), and pineapple peel and chicken manure (25:75) were 24.6; 16.3; and 14.2, respectively. The C/N ratio of compost with a composition of one hundred percent pineapple peel did not meet the standard. Compost with a mixture of pineapple skin and livestock manure (cow and chicken) met the standard. The weight gain of the larvae in each reactor was in the range of forty to fifty times the initial weight of the larvae added to the reactor.